Algorithmic trading and corporate innovation: Evidence from the Tick Size Pilot - Bilinski, Pawel; Karamanou, Irene; Panayides, Marios; Kopita, Anastasia (My University, 2022)
Using the Tick Size Pilot experiment as an exogenous shock to algorithmic trading (AT), we establish a causal positive relation between AT and innovation measured by the quantity and quality of patents. This result reflects that AT increases the efficiency with which prices capture the benefits of innovation, which prompts managers to devote more resources to innovation as the stock price performance influences managers’ compensation and career prospects. Consistently, the relation we document is stronger (i) for firms in which managerial compensation is more closely linked to the share price performance and (ii) for more opaque firms, in which managerial effort is more difficult to infer from accounting information and stock prices play an important monitoring role. The conclusions generalize to other measures of innovation such as R&D spending.
Keywords: Algorithmic trading; Patents; Citations; Innovation